"Effect of Application of Principles of Good Corporate Governance Corporate Financial Performance Against At PT.Duta Cendana Mobilindo Cianjur: Manajemen pemasaran - ENDANG NARYONO, SE., MM (Ekonomedia, 2019)
This research to determine the application of GCG PT.Duta Cendana Mobilindo , development of the company 's financial performance on a PT.Duta Cendana Mobilindo, and to determine the effect of GCG Implementation of the company's financial performance on a PT.Duta Cendana Mobilindo.The method used is the method of ex - post facto . This study uses primary data and secondary data obtained from the financial and non-financial statements of the PT.Duta Cendana Mobilindo . To test the hypothesis used linear regression and correlation Based on the results of the study showed that there is positive between GCG Implementation on the PT.Duta Cendana Mobilindo. The level of closeness of relationship ( correlation ) between the two variables is strong enough , ie r = 0.675 with a correlation coefficient of r > 0 means if GCG Implementation increasing the company's financial performance will increase , and vice versa . The degree of influence is achieved by 45.56 % , and the remaining 54.44 % is influenced by other factors . Meanwhile, through hypothesis testing using t-test , obtained t value = 3.313 and table value of t = 1.987 . Based on the t value , then the value of t is greater than t table located in the rejection of H0 . Results of simple linear regression analysis 2.395 + 0.366 that each increase of 1 ( one point ) Application of the principle of good corporate governance corporate financial performance will increase by 0.366 % . So it can be concluded that the application of GCG has a strong positive influence on the financial performance of the company PT.Duta Cendana Mobilindo.